2020
DOI: 10.3390/molecules25112493
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment with Warfarin Attenuates the Development of Ischemia/Reperfusion-Induced Acute Pancreatitis in Rats

Abstract: In acute pancreatitis (AP), pancreatic damage leads to local vascular injury, manifesting as endothelial damage and activation, increased vascular permeability, leukocyte rolling, sticking and transmigration to pancreatic tissue as well as activation of coagulation. Previous studies have shown that pretreatment with heparin or acenocoumarol inhibits the development of AP. The aim of the present study was to check the impact of pretreatment with warfarin, an oral vitamin K antagonist, on the development of isch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 75 publications
2
24
0
Order By: Relevance
“…Prior studies conducted in the gut have shown that acenocoumarol, inhibits the development of acute pancreatitis [ 48 , 49 ] and enhances recovery in this disease [ 50 ]. Maduzia et al., (2020) [ 51 ], in their study also showed a similar protective effect exhibited by warfarin treatment before the induction of acute pancreatitis in the model employed in the study. Anti-inflammatory, protective and therapeutic effects have been observed in other studies on colons on the administration of coumarins such as daphnetin [ 52 ], 4-methylesculin [ 53 ], or osthole [ 54 ].…”
Section: Discussionsupporting
confidence: 66%
“…Prior studies conducted in the gut have shown that acenocoumarol, inhibits the development of acute pancreatitis [ 48 , 49 ] and enhances recovery in this disease [ 50 ]. Maduzia et al., (2020) [ 51 ], in their study also showed a similar protective effect exhibited by warfarin treatment before the induction of acute pancreatitis in the model employed in the study. Anti-inflammatory, protective and therapeutic effects have been observed in other studies on colons on the administration of coumarins such as daphnetin [ 52 ], 4-methylesculin [ 53 ], or osthole [ 54 ].…”
Section: Discussionsupporting
confidence: 66%
“…Damage to the gastric mucosa is associated with a decrease in blood flow through the gastric mucosa [26], whereas the protection and healing of gastric mucosa is associated with an increase in gastric blood flow [27][28][29]. A similar effect of blood flow organ integrity was observed in other organs of the digestive system such as the duodenum [30], colon [31], liver [31] and pancreas [32]. Disturbances to pancreatic blood flow and pancreatic ischemia play an essential role in the development of acute pancreatitis in different clinical settings [33], including hypovolemic shock [34].…”
Section: Discussionmentioning
confidence: 98%
“…However, osmotic diarrhea caused by enteral nutrition was ignored. Osmotic diarrhea leads to hypovolemia which can disrupt therapy may bring some benefits (Maduzia et al, 2020). However, there may be some risks and side effects, and further research in this field is needed.…”
Section: Discussionmentioning
confidence: 99%